2001
DOI: 10.3171/jns.2001.94.6.0922
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of tumor size and growth in vestibular schwannomas

Abstract: A retrospective analysis of an unselected and sequential series of 433 patients with unilateral VSs was conducted. Tumor size was defined by the largest dimension of the tumor in the cerebellopontine angle, and the size was tested for a relationship with patient age and sex. In a subgroup of 231 patients in whom data were available, tumor size was also tested for a relationship with tumor cysts or the absence of an internal auditory canal (IAC) component. Some patients underwent a period of surveillance with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 25 publications
2
37
0
2
Order By: Relevance
“…Vestibular schwannoma in younger patients presents with more aggressive characteristics including faster growth 18) and hypervascularity. 15,30) The tumor aggressiveness is related to the severe IAM changes seen in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular schwannoma in younger patients presents with more aggressive characteristics including faster growth 18) and hypervascularity. 15,30) The tumor aggressiveness is related to the severe IAM changes seen in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment protocol is based on the slow growth and static presentation of VS that occurs in many patients and is increasingly used in patients with small and minimally symptomatic tumours. 10,11 This conservative approach is not generally used in tumours > 20 mm and intervention is often indicated in the setting of progressive growth or increasingly symptomatic tumours, independent of tumour size.…”
Section: Introductionmentioning
confidence: 99%
“…However studies also show that dose reduction from 12.5 Gy to 10 Gy were associated with a 6-fold greater incidence of tumour regrowth after SRS. 18 In general the available data suggests the incidence of tumour shrinkage was not significantly affected by the lower doses but it did eliminate all incidence of neuropathies. 5,14,19 Research from Foote et al (2001) 11 analyzing risk factors of SRS, suggested a prescription dose of 12.5 Gy to the tumour margin resulted in the best combination of maximum tumour control and minimum complication rates (this did not seem to be effected by TV).…”
Section: Necrosismentioning
confidence: 96%
“…Doses lower than 10 Gy have not proved effective in maintaining tumour control. 18 In general the available data suggests the incidence of tumour shrinkage was not significantly affected by the lower doses but it did eliminate all incidences of neuropathies. 5,14,19 The vast majority of published research establishes SRS as a viable alternative to microsurgical resection for VS.…”
Section: Literature Appraisalmentioning
confidence: 96%